(3QSGdI aj GdVQH hGdbSeIs
(3ChdgG (B:s
(3agPg deY jVWQEdi eYQaJgG ef jQjO GdRhY ai GdaQGFV Ef GdCYOGO GdCUdjI KdGKI CfhGY s
(3BNQgG (B:s
(3HRjGOI KdGKI ai GdebShe aJUjQ KdKeGFg hSJjf hGdMGUd s
(3GfXQ fSNI CNQi HYfhGf deY jSjQI ef Yde GdMSGH dfaS GdecJHI JMJ Qbe (B218 (3QjGVjGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs